2007
DOI: 10.1016/j.bcp.2007.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Treating schizophrenia symptoms with an α7 nicotinic agonist, from mice to men

Abstract: Current antipsychotic treatments fail to fully address the range of symptoms of schizophrenia, particularly with respect to social and occupational dysfunctions. Recent work has highlighted the role of nicotinic in both cognitive and attentional deficits as well as deficient processing of repetitive sensory information. The predilection for schizophrenia patients to be extremely heavy cigarette smokers may be related to their attempt to compensate for a reduction in hippocampal α7 nicotinic cholinergic recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(100 citation statements)
references
References 122 publications
5
95
0
Order By: Relevance
“…Importantly, although the former characteristic of this drug is in line with many reports on a7 agonists (Arendash et al, 1995;Levin et al, 1999;Meyer et al, 1998;Olincy and Stevens, 2007;Pichat et al, 2007;Timmermann et al, 2007;Wishka et al, 2006), the latter capacity to the best of our knowledge is demonstrated here for the first time. Thus, this study suggests that a7-nAChR (partial) agonists can be viewed as promising targets not only for cognitive impairments in schizophrenia, but for treating the wide spectrum of symptoms in schizophrenia, including positive symptoms.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Importantly, although the former characteristic of this drug is in line with many reports on a7 agonists (Arendash et al, 1995;Levin et al, 1999;Meyer et al, 1998;Olincy and Stevens, 2007;Pichat et al, 2007;Timmermann et al, 2007;Wishka et al, 2006), the latter capacity to the best of our knowledge is demonstrated here for the first time. Thus, this study suggests that a7-nAChR (partial) agonists can be viewed as promising targets not only for cognitive impairments in schizophrenia, but for treating the wide spectrum of symptoms in schizophrenia, including positive symptoms.…”
Section: Resultssupporting
confidence: 91%
“…We show that SSR180711 was able to alleviate abnormally persistent LI produced by acute MK801 and neonatal NOS blockade; these models are believed to model cognitive aspects of schizophrenia and the activity here was consistent with previous findings with a7-nAChR agonists (Arendash et al, 1995;Hashimoto et al, 2008;Levin et al, 1999;Meyer et al, 1998;Olincy and Stevens, 2007;Pichat et al, 2007;Timmermann et al, 2007;Wishka et al, 2006). Rather unexpectedly SSR180711 potentiated LI in normal rats and reversed amphetamine-induced LI disruption, two models considered predictive of activity against positive symptoms of schizophrenia (Gray et al, 1991;Kilts, 2001;Lipska, 2004;Lipska and Weinberger, 2000;Moser et al, 2000;Powell and Miyakawa, 2006;Smith et al, 2007;Weiner, 1990Weiner, , 2003 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…208,209 A large body of evidence supports the involvement of neuronal nAChRs in cognitive functions. For example, selective-a7 agonists show efficacy in learning and memory tasks in animals 40 and a role of the a4b2-subunit in cognition is supported by KO and antagonist studies. 20 Thus, genetic variations in nAChRs that influence neurocognitive functions may affect smoking behavior through this mediation, as discussed above for personality traits.…”
Section: General Overviewmentioning
confidence: 98%
“…39 a7-nAChRs may have a role in cognitive deficits in schizophrenia; in a small trial the a7-nicotinic agonist, anabaseine, appeared to have positive effects on neurocognition in patients with schizophrenia. 40 The use of nicotinic agonists or antagonists in these and other CNS disorders is under intense research. The neurobiology of ND The neurobiology of dependence on nicotine and other drugs of abuse is related to the brain limbic system.…”
Section: Neuronal Nachrs Nachr Subunitsmentioning
confidence: 99%